Kepastian Hukum Business Judgment Rule Dalam Memberikan Perlindungan Hukum Bagi Direksi Perseroan - Lina Husnul Khairiyyah; Heru Sugiyono (Universitas Semarang, 2025)
This study aims to examine legal certainty and the accountability of directors in making business decisions through the application of the Business Judgment Rule (BJR) doctrine. The background of this research stems from the high risk of criminalization against directors who act in a business capacity, even though they have acted in good faith. The urgency of this research lies in the need for legal certainty that can provide protection for directors so that they remain bold in making strategic decisions without fear of legal threats. This study uses a normative juridical method with a case approach, namely Decision No. 12/Pid.Sus-TPK/2024/PN Jkt.Pst related to LNG procurement by Pertamina. The results of the analysis show that the BJR doctrine has the potential to provide legal protection for directors, as long as business decisions are made in good faith, with due care, and without conflicts of interest. However, this protection is conditional because it can still be set aside in the event of a violation of the principles of GCG and fiduciary duty. In Decision No. 12/Pid.Sus-TPK/2024/PN Jkt.Pst, BJR's defense was rejected due to procedural violations, such as the absence of approval from the Board of Commissioners and the General Meeting of Shareholders, as well as the absence of adequate risk assessment and technical analysis. The novelty of this study lies in its normative analysis of the application of BJR in criminal cases involving state-owned enterprises, which has not been widely studied in Indonesian legal literature. The consistent application of GCG and fiduciary duty principles is key to achieving legal certainty and protecting directors from future legal risks. Penelitian ini bertujuan untuk menelaah kepastian hukum dan pertanggungjawaban direksi dalam mengambil keputusan bisnis melalui penerapan doktrin Business Judgment Rule (BJR). Latar belakang penelitian ini berangkat dari tingginya risiko kriminalisasi terhadap direksi yang bertindak dalam kapasitas bisnis meskipun telah beritikad baik. Urgensi penulisan terletak pada kebutuhan akan kepastian hukum yang mampu memberikan perlindungan bagi direksi agar tetap berani mengambil keputusan strategis tanpa rasa takut terhadap ancaman hukum. Dalam penelitian ini metode yang digunakan yaitu yuridis normatif dengan fokus pada pendekatan kasus, khususnya melalui Putusan No. 12/Pid.Sus-TPK/2024/PN Jkt.Pst terkait pengadaan LNG oleh Pertamina. Dari analisis yang dilakukan, terlihat bahwa doktrin BJR berpotensi memberikan perlindungan hukum bagi direksi, sepanjang keputusan bisnis dilakukan dengan itikad baik, kehati-hatian, dan tanpa konflik kepentingan. Namun, perlindungan tersebut bersifat kondisional karena tetap dapat dikesampingkan apabila terjadi pelanggaran terhadap prinsip GCG dan fiduciary duty. Dalam Putusan No. 12/Pid.Sus-TPK/2024/PN Jkt.Pst, pembelaan BJR ditolak karena terdapat pelanggaran prosedural, seperti ketiadaan persetujuan Dewan Komisaris dan RUPS, serta absennya kajian risiko dan analisis teknis yang memadai. Kebaruan penelitian ini terletak pada analisis normatif terhadap penerapan BJR dalam perkara pidana korporasi BUMN, yang sebelumnya belum banyak dikaji dalam literatur hukum Indonesia. Penerapan prinsip GCG dan fiduciary duty secara konsisten menjadi kunci terwujudnya kepastian hukum dan perlindungan direksi dari risiko hukum di masa mendatang.